(untitled) (Gaceta de Ciencias Veterinarias, 2019)
ABSTRACT Obtaining cattle that express adaptability and efficient production in tropical environments is the objective in dual-purpose livestock research. In order to evaluate the genetic and non-genetic effects that affect the variation in milk production in dual-purpose cows, 3722 lactation records adjusted to 244 days (P244) of 1334 cows, belonging to a farm located in the municipality of La Ceiba, Trujillo State were analyzed. Model I, allowed to evaluate the non-genetic and genetic effects that affect the variation of P244, establishing as fixed effects: month of calving (MP), year of calving (AP), age at calving (EP), number of calving (NP), and racial group (GR), and as random effects: father, mother of the cow, and residual, being evaluated through an analysis of variance using mixed models methodology of the statistical package SAS®. Model II determined the components of (co) variances, genetic and non-genetic parameters, using a univariate animal model with the set of MTDFREML programs. Considering as fixed effects, those that were significant (P <0.05) of model I: AP, EP, NP and GR. The random effects that were considered: the animal, the permanent environment of the cow and the error. Estimation of the additive genetic variance (σ2a), proportions of the total phenotypic variance (σ2F) due to permanent environmental variance of the cow (σ2Ap), residual variance (e2), inheritance index (h2), and repetition coefficient (ri). Obtaining that for P244 the adjusted average was 1562.26 ± 150.06 kg. All the fixed effects were significant (P <0.05), except for the month of calving. The univariate model estimates of σ2a, σ2Ap, e2, σ2F, h2 and ri for P244 were: 55970, 101127, 118896, 275993, 0.20, and 0.56, respectively. The P244 is highly affected by environmental and genetic factors. Keywords: Livestock dual purpose, milk production, genetic effects, genetic parameters, inheritance index.